2002
DOI: 10.1097/00042737-200204000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of solids in cirrhotic and peritoneal dialysis patients: influence of peritoneal volume load

Abstract: In alcoholic cirrhotic patients with ascites, gastric emptying of solids is delayed, independently of the volume of ascites. In peritoneal dialysis patients, gastric emptying was delayed when "full" and normalized after drainage of the dialysate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 7 publications
4
17
0
1
Order By: Relevance
“…In our series 50% of patients with cirrhosis were found to have delayed gastric emptying which is in line with results previously presented from our group [74] and others [75][76][77]. However, the increased proximal stomach relaxation observed in our patients does not seem to be associated with delayed gastric emptying.…”
Section: Gastric Sensorimotor Dysfunction (Ii)supporting
confidence: 93%
See 3 more Smart Citations
“…In our series 50% of patients with cirrhosis were found to have delayed gastric emptying which is in line with results previously presented from our group [74] and others [75][76][77]. However, the increased proximal stomach relaxation observed in our patients does not seem to be associated with delayed gastric emptying.…”
Section: Gastric Sensorimotor Dysfunction (Ii)supporting
confidence: 93%
“…Transit studies in patients with liver cirrhosis have shown contradictory results for gastric emptying [74][75][76][77][78][79][80][81]. In our series 50% of patients with cirrhosis were found to have delayed gastric emptying which is in line with results previously presented from our group [74] and others [75][76][77].…”
Section: Gastric Sensorimotor Dysfunction (Ii)supporting
confidence: 87%
See 2 more Smart Citations
“…A relação entre o retardo no EG e a diálise peritoneal e o volume e a composição do líquido de diálise tem sido objeto de muitos estudos clínicos 18 . Existe consenso quanto a existência de retardo em pacientes com IRC em diálise peritoneal 4,19,10 e de que este retardo não está relacionado ao volume do líquido infundido18 mas à absorção de substâncias presentes no líquido de diálise 21 .…”
Section: Discussionunclassified